Fuzzy Self-tuning PI Controller for Field-weakening Control System of an Axial Flux Switching Permanent Magnet Motor - Hamid Radmanesh; Javad Rahmani Fard (AUT Journal of Electrical Engineering, 2021)
In this paper, based on the vector control of axial field flux switching permanent magnet (AFFSPM) motor, an optimized field-weakening control method of AFFSPM motor is proposed. A new AFFSPM motor with 12 stator slots (S) and 19 rotor poles (P) is taken as the object to simulate and optimize the flux-weakening speed control. The AFFSPM motor adopts constant torque control with the maximum torque per ampere below the base speed, which reduces motor losses, improves the efficiency of the inverter and adopts constant power and sub-regional speed control above the rated speed. By combining the cross-axis current and direct-axis current in the flux weakening control method, the power factor of the AFFSPM motor can be improved and speed range can be extended. By considering the speed fluctuation in field weakening control, and the fuzzy self-tuning PI control method is proposed to improve the performance of the AFFSPM motor field weakening control. To verify the feasibility of proposed control method, Co-Simulation is used. Finally, the control algorithm of the drive system is implemented in a prototype of AFFSPM motor.